Cigány gyermekek úja a felsőoktatásig, az értelmiségivé válásig - Farkas Marietta (2017)
This essay focuses on the changes of Gypsy identity and eduction. In order to understand their motivations it is important to put into context of school, education, and their parents’ and teachers’ support. We need to take into account the life of Romani people in Hungary, the succesful and unseccessful integration, focusing on personal cases and stories. A part of the people who studying in the higher education as gypsy. We can get to know their motivations, experience about education, and the situation of discrimination. We can say something was changed in their life, and family. Their family supported them, and give motivation which changed their mind and future. Romani people had differnt ways of life, but we can say, most of them had connections with the Hungarian culture and identity. They have double identity, one of them is the Roma identity, the other is the Hungarian identity. It is useful to highlight important facts of their life of education, they had a teacher who supported and helped them. They have the different experience but we have to research it so we can understand their life and identity.
Keywords: Társadalomtudományok; Szociológia